The use of tree diagram method on arrange sentences Exercise to improve students’ vocabulary at the Fourth grade students in sdn 37 lubuk gambir - Ermaniza Ermaniza (Fakultas Sastra Universitas Ekasakti, 2017)
The fluency of a person's language is closely related to the vocabulary he has. The more vocabulary you have, the larger the horizon you have. This is where the vocabulary is clearly visible. In general, the increased vocabulary of school-aged children because of the influence of the surrounding environment, such as getting a lesson in school directly reading, listening to teachers or friends who are talking and others. Based on the available information, the number and quality of vocabulary of elementary school age children is running rapidly. SD curriculum states that the vocabulary that must be mastered by primary school children is 6,000 words. The vocabulary has been determined based on a certain level, (Class I to VI). But the subject of the determination is not clear so it hasnot been seen how the relationship between the word one with another word. Speaking of vocabulary almost always implies meaning. Understanding vocabulary means relating to the potential to recognize the sense contained in the word.Thus the form and meaning of words used in everyday life must be linked to the underlying context